APPLYING MURDER TECHNIQUE TO IMPROVE STUDENTS’ READING COMPREHENSION OF THE SEVENTH GRADE STUDENTS OF SMP SANTO THOMAS 1 MEDAN IN THE ACADEMIC YEAR OF 2020/2021 - Pandiangan, Siska Ria; Sinaga, Anna Stasya Prima Sari; Ginting, Fiber Yun A. (Kairos English Language Teaching Journal, 2021)
The aim of this study is to find whetever Murder technique works effectively on improving students’ reading comprehension and to describe the students’ responses towards the application of Murder technique in the learning teaching processes of reading comprehension. The subject of the study in the seventh grade students of SMP Santo Thomas 1 Medan in the Academic Year of 2020/2021 consisting 32 students of class VII-A. This study was conducted by applying Classroom Action Research (henceforth CAR). The result of the test showed that the students’ mean score in pre-test is 55,00 with 16% of students got ≥ 70, in formative test is 68,13 with 38% of students got score ≥ 70, and 83,13 in post test with 100% of students got score ≥ 70. The qualitative data analysis showed that the students’ responses after being taught by using Murder Technique are very good. The percentage students who strongly agree is 26 (81%), agree is 27 (84%), there is no students choose strongly disagree and disagree. It is suggested that the English teachers use Murder Technique as an alternative technique in teaching reading to the students in Junior High School in order to improve their students’ reading comprehension.